2018
DOI: 10.1016/j.biteb.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Systematic procedure and framework for synthesis and evaluation of bioethanol production processes from lignocellulosic biomass

Abstract: Bioethanol from lignocellulosic feedstock rises as a promising alternative to replace liquid fossil fuels in the energy market for the next years. However, the variety of available biomass combined with the necessity of possible pretreatments and their particular features make it difficult to clearly identify the favorable process routes. In this study a systematic approach consisting of seven steps was proposed to obtain possible and feasible alternatives for the conversion of lignocellulosic biomass into bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Lignocellulosic biomass, the most abundant, inexpensive alternative to food crop resources, represents a possible feedstock for renewable chemicals and fuels [1]. However, inhibitors (furans, weak acids and phenols) are inevitably formed during pretreatment and hydrolysis of lignocellulosic substrates [2] and are harmful to Zymomonas mobilis growth and ethanol fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulosic biomass, the most abundant, inexpensive alternative to food crop resources, represents a possible feedstock for renewable chemicals and fuels [1]. However, inhibitors (furans, weak acids and phenols) are inevitably formed during pretreatment and hydrolysis of lignocellulosic substrates [2] and are harmful to Zymomonas mobilis growth and ethanol fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific advancement in genetics, biotechnology, engineering and process chemistry have yielded 'biorefinery,' a novel manufacturing concept. It converts renewable agro-wastes / biomass into biofuels, nutrients and by-products while integrating different technologies [11]. It offers the possibility for sustainable production of biopower and biomaterials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental impact is calculated by subtracting environmental costs from environmental benefits, while MESP takes into account the annual capital cost investment, annual operating cost, and cost of lignocellulosic feedstock. Contrary to da Silva et al [60], they found that corn stover has a negative environmental benefit due to its low lignin content that allows a lower substitution of fossil energy sources. However, it should be noted that they resulted in much lower values, e.g., only 14.1% lignin and 29.6% cellulose content, compared to the other study (15.5% and 37.6%, respectively).…”
Section: Lignocellulosic Ethanol Studiesmentioning
confidence: 64%
“…According to the comparison of da Silva et al [60], spruce is the cheapest 2G raw material; however, due to its relatively low convertible sugar (cellulose and hemicellulose) content, Eucalyptus-based ethanol is the cheapest option. By using the theoretical ethanol yield, this would result in 0.1376 USD/L.…”
Section: Lignocellulosic Ethanol Studiesmentioning
confidence: 99%